Determination of Urinary Neopterin/Creatinine Ratio to Distinguish Active Tuberculosis from Latent Mycobacterium tuberculosis Infection. (28th June 2016) - Eisenhut, Michael; Hargreaves, Dougal S.; Scott, Anne; Housley, David; Walters, Andrew; Mulla, Rohinton
Abstract : Background . Biomarkers to distinguish latent from active Mycobacterium (M.) tuberculosis infection in clinical practice are lacking. The urinary neopterin/creatinine ratio can quantify the systemic interferon-gamma effect in patients with M. tuberculosis infection. Methods . In a prospective observational study, urinary neopterin levels were measured by enzyme linked immunosorbent assay in patients with active tuberculosis, in people with latent M. tuberculosis infection, and in healthy controls and the urinary neopterin/creatinine ratio was calculated. Results . We included a total of 44 patients with M. tuberculosis infection and nine controls. 12 patients had active tuberculosis (8 of them culture-confirmed). The median age was 15 years (range 4.5 to 49). Median urinary neopterin/creatinine ratio in patients with active tuberculosis was 374.1 micromol/mol (129.0 to 1072.3), in patients with latent M. tuberculosis infection it was 142.1 (28.0 to 384.1), and in controls it was 146.0 (40.3 to 200.0), with significantly higher levels in patients with active tuberculosis (p < 0.01 ). The receiver operating characteristics curve had an area under the curve of 0.84 (95% CI 0.70 to 0.97) (p < 0.01 ). Conclusions . Urinary neopterin/creatinine ratios are significantly higher in patients with active tuberculosis compared to patients with latent infection and may be a significant predictor of active tuberculosis in patients with M. tuberculosis infection.